Rubble & crew. On the job! [videorecording (DVD)] (Paramount, 2025)
"What's more fun than a pup in a construction vehicle? Lots of pups in lots of construction vehicles. Rubble and his family - Aunt, Grandpa, cousins and all - are working hard to make their town, Builder Cove, a ter-ruff-ic place to live." --